2022
DOI: 10.36923/jicc.v22i4.38
|View full text |Cite
|
Sign up to set email alerts
|

Effects of YouTube Culture on Academic Performance among Students in Jordan: A Structural Equation Modeling Study

Abstract: The global technological transformation has greatly changed and improved almost every part of our life. Notably, today, social media influences us even for the basic necessities of life, such as education. By keeping the importance of social media in education, this research also focuses on the effects of YouTube culture in improving students' academic performance in Jordan. The researchers used Structural Equation Modeling (SEM)as the study relies on a self-proposed conceptual model. Results revealed that soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In the first step, the instrument was checked for normality, then the external model was tested, and once it was confirmed that the external model was suitable, Smart PLS3 was used to analyze the internal model after it had been confirmed that the external model was suitable. (Habes, Al-Adwan, et al, 2022;Habes, Ali, et al, 2022;Wang et al, 2022).The procedures that have been followed for analyzing the collected data are mentioned in the analysis portion.…”
Section: Methodsmentioning
confidence: 99%
“…In the first step, the instrument was checked for normality, then the external model was tested, and once it was confirmed that the external model was suitable, Smart PLS3 was used to analyze the internal model after it had been confirmed that the external model was suitable. (Habes, Al-Adwan, et al, 2022;Habes, Ali, et al, 2022;Wang et al, 2022).The procedures that have been followed for analyzing the collected data are mentioned in the analysis portion.…”
Section: Methodsmentioning
confidence: 99%
“…Initially the reliability and validity of the instrument was analyzed, followed by identifying the direct impacts and finally the mediating effects. Habes, Al-Adwan, et al, 2022;.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…This coding framework has also been demonstrated to apply to the construction of messages in social media. For example, the themes encoded in the Nature Is Speaking campaign on YouTube (Olausson, 2020) and the content posted by Latvian populist parties on Facebook (Rozukalne, 2020;Habes, Al-Adwan, Al Rabat, Shatnawi, & Al Jwaniat, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%